Is PONV still a problem in pediatric surgery: a prospective study of what children tell us - Messerer, Brigitte; Stijic, Marko; Sandner-Kiesling, Andreas; Brillinger, Johanna M.; Helm, Jasmin; Scheer, Jacqueline; Strohmeier, Christof Stefan; Avian, Alexander (Frontiers in Pediatrics, 2023)
Background: Postoperative nausea and vomiting (PONV) is an unpleasant complication after surgery, along with pain. Given the high prevalence in pediatric patients, it is important to explore the main risk factors leading to PONV in order to optimize strategies. We aimed (1) to determine the prevalence of PONV on the day of surgery by interviewing children, (2) to assess PONV prevalence in the recovery room and on the ward through nursing records and (3) to collect information on PONV risk factors on the day of surgery and the following postoperative days. We wanted to investigate real life and not an artificially designed study.Methods: Prospective analysis (according to STROBE guidelines) of PONV on the day of surgery and the following postoperative days by evaluation of demographic and procedural parameters and interviewing our children. Six hundred and twenty-six postoperative children and adolescents aging from 4 up to 18 years were interviewed after surgery on the ward by means of a questionnaire as from an age of 4 children can participate in an outcome-based survey.Results: On the day of surgery, multivariable independent predictors of PONV were type of surgery (p = .040) with the highest OR in patients with procedural investigations (OR 5.9, 95%CI: 1.8-19.2), followed by abdominal surgery (OR 3.1, 95%CI: 0.9-11.1) when inguinal surgery was used as the reference category. In addition, the amount of fentanyl used during anesthesia (µg per kg body weight) (OR 1.4, 95%CI: 1.1-1.8), intraoperative use of piritramide (OR 2.6, 95%CI: 1.5 -4.4) and diclofenac (OR 2.0, 95%CI: 1. 3-3.1) opioid administration in the recovery room (OR 3.0, 95% CI: 1.9 -4.7) and piritramide use on the ward (OR 4.5, 95%CI: 1.7-11.6) were identified as predictors.Conclusions: Main risk factors for PONV include administration of opioids intraoperatively, during the recovery room stay and at the ward, non-opioids (diclofenac) intraoperatively and type of surgery Real life data demonstrated that in clinical praxis, there is a gap between adherence to guideline and the use of antiemetic prophylaxis in surgeries that are generally not associated with a high PONV prevalence.Further effort is needed to improve the procedures and so outcome.